Introduction to Latin America twenty-first century challenges - Kirby, Peadar (SAGE, 2003)
Placing Latin America within a genuinely global context, this text introduces the debates and impacts of globalization neo-liberalism, democratization and the environment to provide an introduction to the political, social and economic forces shaping this essential region of undergraduate study.